Pemanfaatan Media Digital dalam Pembinaan Ibadah Siswa di SDS IT Al Fatih - Husna, Ainayya; Matsum, Hasan (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study is based on the importance of religious education, particularly in nurturing students' worship practices, as a foundation for character development from an early age. In today's digital era, the utilization of digital learning media has become a promising strategy to improve the quality of teaching, including in Islamic Religious Education. This research aims to examine the use of digital learning media in supporting students' worship development at SDS IT Al Fatih, evaluate its effectiveness, and identify the challenges encountered during implementation. A qualitative approach was employed, using data collection techniques such as in-depth interviews, participatory observations, and documentation.The findings reveal that digital media, such as educational videos, learning applications, and web-based platforms, significantly enhance students’ motivation and understanding of worship-related materials. Teaching strategies combined with digital media, such as expository methods and discussions, positively impact student engagement and learning outcomes. However, several challenges were identified, including limited technological infrastructure, varying levels of digital literacy among students and teachers, and time constraints in delivering the learning content. The successful integration of digital media is highly dependent on the availability of school facilities and teachers’ competence in utilizing educational technology. In conclusion, this study affirms that incorporating digital media in worship learning significantly improves the quality of Islamic education at the elementary level. Therefore, a more structured and sustainable implementation strategy is necessary to ensure that digital media effectively supports interactive, contextual, and meaningful learning experiences.